PERSENTASE KARKAS DAN MORTALITAS BROILER DAN AYAM KAMPUNG YANG DI BERI LIMBAH AMPAS PATI AREN TIDAK DIFERMENTASI DAN DIFERMENTASI DALAM RANSUM - Aisyah Nurmi; Melia Afnida Santi; Nurainun Harahap; Muharram Fajrin Harahap (JURNAL ILMIAH PETERNAKAN TERPADU, 2018)
The objectives of this research were to study the percentage of carcass of broiler and native chicken given arenga waste fermentation by Saccaromyces cerevisiae and to study arenga waste unfermentation in the ration. Sixty of broiler chickens Arbor Acres strain and sixty native chickens were divided into four dietary treatments and three replications (10 birds/replicate). The design of this experiment was completely randomized design factorial 2x2, with factor A was feeding (A1 : arenga waste unfermented, A2 : arenga waste fermented), and factor B was chicken species (B1:native chickens, B2:broilers). The variables observed were:  (1) body weight, (2) carcass, (3) percentage of carcass, and (4) Mortality.The purposes of this study  were to look at the effectiveness of rations and species of chicken used for the percentage of carcass and mortality. The results showed that there was no interaction (P> 0.05) between the fed arenga waste fermented or unfermented 2.5% in the ration,and  the type of chicken on weight, carcass and carcass percentage, but there was an interaction on mortality (P<0.01). The fed had no significant (P>0,05) effect on weight, carcass, and carcass percentage, but  percentage, but significant effect (P <0.05) on mortality.  Types of chickens had a significant effect (P <0.05) on weight, carcass, percentage  of carcass and mortality. The mortality rate with unfermented arenga waste was high enough, especially in broiler chickens, but it can be tolerated  on native chicken and broilers with saccaromyces cerviseae fermented arenga waste. Keywords : Arenga Waste, Fermentation Arenga Waste, Native Chickens, Broiler